(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
MSME economic activity in Indonesia is rising after a pandemic. The non-cash payment system is more in demand by consumers as well as manufacturers. The non cash payment system of QRIS is increasingly used in business transactions. Therefore, this study aims to analyze the determining factors of financial behavior of UMKM owners of QRIS users. A total of 204 respondents were owners of small micro-enterprises using QRIS from Kota Medan, Makassar and Bali. The defining variables used are the age, age of enterprise, education and religion of the enterprise owner. Data analysis techniques use double linear regression with SPSS tools. Research results show that age and education have an impact on the financial literacy of UMKM users QRIS. The interesting thing about this finding is that the age of generation X UMKM owners has the greatest impact on financial literature.